Hubungan Tingkat Pengetahuan Dengan Sikap Remaja Terhadap LGBT Di SMAN 6 Kota Tangerang Selatan - Pasaribu, Sondang Deri Maulina; Suheti; Royani; Puspitaloka, Rhelisa (STIKes IMC Bintaro, 2023)
Introduction : LGBT is a sexual deviance which means that lesbian means women like women, gay means men like men, bisexual means someone who likes both genders simultaneously, and transgender means someone who changes his appearance to be inconsistent with his original identity. According to the United Nations, there are already more than 3 million LGBT people in Indonesia. Factors that can influence a person's deviant behavior are knowledge, attitude, motivation, religious observance, and perceptions of LGBT. Attitude is a form of evaluation or reaction to one's feelings towards LGBT. The purpose of research : To determine the relationship between the level of knowledge of adolescents and LGBT prevention behavior in SMA Negeri 6 Kota Tangerang Selatan. Research methods : This type of research is a quantitative approachcoss sectional. Sampling technique using simple random sampling by voting through the applicationrandom generator. The number of samples is 86 people. Results of research : Based on the results of the study, it was found that most of the youth had a less knowledge level of 44 respondents (51.2%). And experiencing attitudes towards LGBT is less as much as 46 respondents (53.5%). Results of bivariate analysis with testwho squaresshow valuep value 0.001 (p<0.005) OR equal to26,917 (8,479-85,452). Conclusion : There is a significant relationship between the level of knowledge and attitudes of youth towards LGBT at SMAN 6 Kota Tangerang Selatan in 2022. Suggestion : It is hoped that the school can provide further information through counseling about problems in sexual deviation..